Antiviral activity of Cymbopogon nardus methanol fractions against measles disease virus - Reagan Entigu, ak Linton @ Jerah (Universiti Malaysia Sarawak (UNIMAS), 2014)
Measles disease virus has been a major concern since it has not been able to be fully eradicated. Vaccine was introduced and surveillances were conducted for the disease. The disease still claims the life of thousands of children especially in developing countries where vaccine and drugs are not easily accessible to the people. Active constituents from medicinal plant products were studied and their bioactivities were identified. The chemical structure allows researchers to better understand the mechanisms of infection, hence enable mass production of the compound either naturally or synthetically activity-enhanced compound. Methanol fractions and subfractions of Cymbopogon nardus, serai wangi, were tested for antiviral activity against measles virus and their cytotoxicity against ovarian cancer cell line, Caov3 compared to Vero cell line were evaluated. The assays were carried out based on bioassay-guided fractionation and the antiviral mechanism was evaluated. The fraction C2 showed the highest activity at post-infection assay and its subfraction C2.1 was the most active. The subfraction was run on thin-layer chromatography plate to separate the constituents, yielding four individual spots where the second spot, C2.1b has the active antiviral and highly cytotoxic toward Caov3 cell line. The GC/MS analysis revealed that it contained octadecanoic acid, methyl ester, a fatty acid. The findings showed that the methanol fraction of C. nardus possessed potential antiviral activity and selective toxicity against ovarian cancer cell. Further study on active compounds of the C. nardus against different ii viruses, human cell lines and also other bioactivities such as antimicrobial should be carried out.